Sensitive and reliable PCR and sequencing used to detect p53 point mutations in fine needle aspirates of the breast. Issue 7 (July 1996) - Howes, G P; Stephenson, J; Humphreys, S
Abstract : AIMS/BACKGROUND: Fine needle aspirates (FNAs) of breast lesions are now a routine investigation and prognostic information at this stage would be useful for accurate management, p53 gene status can be used as prognostic indicator, an abnormal genotype being associated with high grade, oestrogen receptor poor tumours. As the main disadvantage with FNA is poor cellularity, the objective of this study was to develop a sensitive and reliable method for the assessment of the p53 status of the lesion. METHODS: Using PCR and subsequent direct sequencing, a method was developed that enables analysis of the p53 gene from relatively few malignant or suspicious cells in a background of normal cells. RESULTS: This method is both reproducible and sensitive. The sensitivity of the method is demonstrated and a mutant cell can be seen in a background of 90% of normal wild type cells. A mutation, not previously described in breast cancer, is also reported in a symptomatic FNA. CONCLUSIONS: This methodology is reliable and effective on samples with both variable cell numbers and quality of preservation, allowing it to be applied successfully to diagnostic cytology.